Modeling Meat Consumption and Short-Term Prospects - Bozhidar Ivanov; Daniela Dimitrova (Икономика и управление на селското стопанство, 2021)
The prospects for development in the short term of the consumption of four main types of meat(beef, pork, poultry and lamb) are presented. The results are based on the developed partially equilibrium dynamic model „Meat”. The aim of the present study is to substantiate the reliability of the approaches used to model consumption in these types of meat, revealing the substitution relationships between them. The trends in the levels of individual consumption as well as the annual variations are considered. The main independent variables that are included in the consumption equation for the different types of meat are distinguished. The elasticities, which determine the changes in the consumed quantities as a result from substitution dependencies between resultative value and independent variables are indicated. The applied approach for calibration of the model, by means of subjectively determined coefficients, allowing to derive a forecast for the individual level of consumption in the short term is demonstrated. The most pronounced is the inverse correlation between retail price and consumption of poultry and pork, where the price elasticity is -0.8. In these two types of meat, the substitution effect is more noticeable, as the increase in the price of pork provokes an increase in the consumption of chicken meat with an elasticity of 0.6. The consumption of pork and lamb changes symmetrically with the in-crease in economic welfare, expressed in terms of GDP per capita, while the increase of beef consumption is the weakest. In the short term, the most serious increase is expected in the consumption of pork.